Graphite/NiO/Ni Electrode for Electro-oxidation of the Remazol Black 5 Dye - Ni Made Wiratini; Triyono Triyono; Wega Trisunaryanti; Agus Kuncaka (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Graphite/NiO/Ni electrode had been fabricated for the electro-oxidation of remazol black 5 dye. The electrode was synthesized by electrodeposition method. Electro-oxidation of 100 ppm remazol black 5 dye was carried out at various concentrations of NaCl, 0.025; 0.05; 0.1; 0.25; and 0.5 M, variations in electro-oxidation time were 15, 30, 45, and 60 minutes, and pH variations were 4, 6, and 8. Cyclic voltammetry test revealed that graphite/NiO/Ni electrode had higher electrocatalytic capability compared to graphite electrode. The X-ray diffraction (XRD) patterns showed the decreasing value of 2θ from 44.6° for Ni to 43.5° for NiO. Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX) showed that NiO/Ni deposited on the graphite surface in the form of solid grains and cracks, FTIR showed that δ(Ni−O) bond appeared at 582–511 cm−1. The decolorization efficiency of remazol black 5 for graphite/NiO/Ni electrode was 100% for 45 minutes of the electro-oxidation process, while the decolorization efficiency of remazol black 5 for graphite electrode was 99.74% for 60 minutes of the electro-oxidation process. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).